The Gonadal Maturity and Gene Expressions of Female Giant Freshwater Prawn (Macrobrachium rosenbergii) after Dietary Administration of Medroxyprogesterone Acetate - Anggraeni, Fajar; Malini, Desak Made; Damanhuri, Joni Haryadi; Syahputra, Khairul; Sopian, Asep; Khasani, Ikhsan; Imron, Imron; Krettiawan, Hary (Faculty of Fisheries and Marine Universitas Airlangga, 2024)
Abstract One of the problems in giant prawn cultivation is female giant prawns laying eggs during rearing. They will incubate their eggs for three weeks so that the energy from the expected feed for growth is used for egg development and other reproductive activities. Giving MPA hormone to giant prawns either by injection or oral could inhibit gonadal maturation and increase growth rate. The maturation process of the prawn ovary consists of the activation of some complex cellular mechanisms involving genes that regulate the stages of oocyte development. This study aimed to evaluate the response of gonadal maturity and the expression of the MrvWD-Kazal gene in giant prawns fed with a diet containing MPA hormone. The design used in this study was a completely randomized design with four treatments and five replications. The treatments were feeding a diet added with MPA with a concentration of 0 mg.kg-1 feed as control (K), 50 mg.kg-1 feed (P1), 100 mg.kg-1 feed (P2), and 150 mg.kg-1 feed (P3). MPA hormone at a concentration of 50-150 mg/kg feed could inhibit the gonadal maturation of female prawns. In 100 mg/kg of feed concentration showed the lowest gene expression level, indicating an inhibition of gonadal maturation molecularly. The administration of MPA hormone through the feed is a recommended method of aquaculture because it is more applicable and effective than by injection, even though it has a non-uniform impact on each individual. Highlight Research Administration of MPA hormone through the feed to female giant freshwater prawns can inhibit the level of gonad maturity. Expression of von Willebrand factor D (vWD) – Kazal gene were analyzed in different levels of prawn maturity Gonadosomatic index and gonadal histology confirmed that different levels of administration of MPA hormone through the feed could affect the gonad development. The administration of MPA hormone through the feed is a recommended method for aquaculture because it is more applicable and effective to inhibit early maturation of prawns.